PENDIDIKAN KARAKTER PADA MADRASAH: IMPLEMENTASI NILAI-NILAI KARAKTER DALAM KEGIATAN EKSTRAKURIKULER DI MADRASAH ALIYAH NEGERI 3 PALEMBANG - Misyuraidah, Misyuraidah; Syarnubi, Syarnubi (Tadrib: Jurnal Pendidikan Agama Islam, 2022)
The purpose of this research is to see the character values instilled in extracurricular activities. Extracurricular activities at Madrasah Aliyah Negeri 3 Palembang are a series of activities carried out outside formal school hours. In this regard, in terms of time, extracurricular activities at Madrasah Aliyah Negeri 3 Palembang are carried out every day, namely: (a) Osis, (b) Pramuka, (c) Paskibra, (d) Rohis and Tahfiz Qura'n, (e) KIR, (f) Robotics, (g) Math Olympiad Club, (h) Economics Olympiad Club, (i) Geography Olympiad Club, (j) Basketball Sports Club, (k) Futsal Sports Club, (l) Volly Sports Club, (m) Ba dminton Sports Club, (n) Takraw Sports Club, (o) Pancak Silat, (p) karate, (q) Islamic Art Studio, (r) Environment/Adiwiyata, (s) Band Group, (t) Journalism and Photography, and (u) PMR.The character education values reflected in the behavior of Madrasah Aliyah Negeri 3 Palembang students are religious character, honesty, tolerance, discipline, hard work, creativity, independence, democratic, curiosity, respect for achievement, friendship, peace love, environmental care, social care and responsibility.